(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted at the Demonstration Farmof the Faculty of Agriculture, University of Khartoum, Sudan, during2012/2013 and 2013/2014 seasons, to determine the magnitude of growthand yield losses in grain sorghum crop due to weed competition, and toevaluate the effects of three herbicides viz, sorgoprim, gesaprim and tankmixture of 2,4-D and gesaprim at three rates of each in addition to aweed-free and a weed- infested treatments i.e. eleven treatments. Theexperiment was laid out in a randomized complete block design with fourreplications. The results showed that when the weeds were left to competewith the sorghum crop throughout the season, the reduction percentages inthe seedlings’ dry weight, plant height and plant shoot dry weight in2012/13 were 55.4, 39,2 and 47.2 respectively; reductions in the sameparameters were 74.4, 39.1 and 45.4 respectively in 2013/14. Untreatedweeds – infested control, coupled with weed index (WI) of 65%–66%,inflicted considerable reductions in crop grain number/ plant of 60.1% in2012/13 and 61.4% in 2013/14, grain weight/plant of 66.3% in 2012/13and 66% in 202013/14 and on yield( ton/ha) by 65% in 2012/13 and by66% in 2013/14. All herbicide treatments irrespective of rate ofapplication, resulted in a good to excellent weed suppression. Herbicidesweed control efficiency (WCE) for 2012/13 and 2013/14 ranged from56% to 99% for broad-leaved weeds and from 39% to 97% for grassyweeds. The mixture tank of 2, 4-D + gesaprim @ 0.76L/ha + 0.6 Kg/hatreated sorghum reduced the WI to 2.5% in 2012/13 and to 3.2% in2013/14 and resulted in values of crop grains number/plant, grains weight/plant and yield significantly comparable to weed-free treatment.